2018
DOI: 10.1186/s12978-018-0566-8
|View full text |Cite
|
Sign up to set email alerts
|

Client satisfaction with family planning services in the area of high unmet need: evidence from Tanzania Service Provision Assessment Survey, 2014-2015

Abstract: BackgroundClient satisfaction has been found to be an important factor for the uptake and continuation of family planning services. This study aimed to examine the current status of and factors associated with client’s satisfaction with family planning services in Tanzania, which has a high unmet need for family planning.MethodsThe study used data from the Tanzania Service Provision Assessment survey of 2014–2015. A facility was classified as having high service readiness for FP if it scored at least 67.7% on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 24 publications
3
28
1
Order By: Relevance
“…The instrument was adapted from previous works of literature. 5,[8][9][10][11][12][18][19][20] Data were collected using a validated and pre-tested structured questionnaire. The questionnaire contained the following: socio-demographic factors of the clients, their health service organization experience, reproductive health history, and provider competence from the four public health facilities.…”
Section: Data Collection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The instrument was adapted from previous works of literature. 5,[8][9][10][11][12][18][19][20] Data were collected using a validated and pre-tested structured questionnaire. The questionnaire contained the following: socio-demographic factors of the clients, their health service organization experience, reproductive health history, and provider competence from the four public health facilities.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…11 Studies from developing countries have found that not being satisfied with family planning services is a prime reason for high rates of discontinuation, reduced utilization of FP services, non-compliance, and high rates of unintended pregnancy. 5,11,12 Evidence from several studies shows that client satisfaction is affected by different factors. Those are; sociodemographic factors: marital status, educational status, and age, 12,13 service provider level factors: provision of information on potential side effects, ensuring privacy, examining during the visit, 8,10,12-14 service organization factors: using educational materials, informed choice, waiting time, urban facilities, the sanitary condition of the room.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that client satisfaction can be an important factor for the uptake and continuation of contraception services. [31][32][33] In order to understand how women perceive the quality of the programme's FP services, annual client exit interviews are conducted at each supported facility to solicit feedback and improve accountability to clients. Results are then used by the programme team to target trainings, supervision, and resources to address gaps identified.…”
Section: Monitoring and Evaluationmentioning
confidence: 99%
“…Several studies have documented poor utilization of family planning services as a result of poor perception of service quality by clients at health facilities [3,6,7], even with relatively low user expectations [8,9,10]. These studies concluded on the need for health services quality improvements that respond to patients needs to improve utilisation.…”
Section: Introductionmentioning
confidence: 99%